Upaya Guru PAI Dalam Meningkatkan Motivasi Belajar Menggunakan Model Problem Based Learning - Fikri Armedyatama (Prodi Pendidikan Keagamaan Islam, 2024)
This study aims to determine the use of the Problem-Based Learning model in improving student learning motivation in PAI subjects at SMPN 1 Kamang Magek. Using a qualitative method with a descriptive approach, data were collected through observation, documentation, and interviews. The results indicate that: (1) The application of the Problem-Based Learning model to increase student learning motivation has gone well. (2) The implementation carried out by PAI teachers has fulfilled the steps of the Problem-Based Learning model well, including preparing and delivering material, providing stimulus and response, student assignments, and evaluation (3) PAI teachers have been effective in increasing the learning motivation of class VIII students at SMPN 1 Kamang Magek even though they have shortcomings.